Characteristics of Susac syndrome: a review of all reported cases - Dörr, Jan Rafael; Krautwald, Sarah; Wildemann, Brigitte; Jarius, Sven; Ringelstein, Marius; Duning, Thomas; Aktas, Orhan; Ringelstein, Erich Bernd; Paul, Friedemann; Kleffner, Ilka (Nature reviews. Neurology, 2013)
Susac syndrome is an important differential diagnosis in many neurological disorders, but our understanding of this rare disease has largely been limited to reports of single cases and small case series. In this article, Dörr and colleagues review all reported cases of Susac syndrome to provide a comprehensive overview of demographic, clinical and diagnostic data on this disorder. On the basis of their findings, Dörr et al. make recommendations for diagnosis and management of individuals with suspected Susac syndrome.
Gesehen am 17.12.2020